COMPARATIVE ANALYSIS AND PRACTICAL IMPLEMENTATION OF THE RESULTS OF SUBGRADE CALCULATIONS WITH VARIATION OF DYNAMIC EFFECT - Buhaiov, A. K.; Petrenko, V. D.; Tiutkin, O. L.; Tsepak, S. V. (Science and Transport Progress, 2003)
The results of dynamic influence on the subgrade work are shown in the article at the transition to high speed motion. The intrusion of a finite element method in calculations during the innovation of real facilities is done.